Group virtue The importance of morality (vs. competence and sociability) in the positive evaluation of in-groups. [article]. - Leach, Colin Wayne
Although previous research has focused on competence and sociability as the characteristics most important to positive group evaluation, the authors suggest that morality is more important. Studies with preexisting and experimentally created in-groups showed that a set of positive traits constituted distinct factors of morality, competence, and sociability. When asked directly, Study 1 participants reported that their in-group's morality was more important than its competence and sociability. An unobtrusive factor analytic method also showed morality to be a more important explanation of positive in-group evaluation than competence or sociability. Experimental manipulations of morality and competence (Study 4) and morality and sociability (Study 5) showed that only in-group morality affected aspects of the group-level self-concept related to positive evaluation (i.e., pride in, or distancing from, the in-group). Consistent with this findings, identification with experimentally created (study 2b) and preexisting (studies 4 and 5) in-groups predicted the ascription of morality, but not competence of sociability, to the in-group. -- (from the author)